Nanoemulsion: An Advanced Vehicle For Efficient Drug Delivery - Ali, Asad; Ansari, Vaseem Ahamad; Ahmad, Usama; Akhtar, Juber; Jahan, Afroz (Drug Research, 2017)
Advanced drug delivery system has now gained preference over the conventional drug delivery system. One such research is nanoemulsion which is famous among the researchers because of ease of formation, stability, clarity, increased absorption rate leading to increasing in bioavailability and potential to form a formulation with both lipophilic as well as the hydrophilic drug. Long lasting stability (up to years) and ability to encapsulate both lipophilic and hydrophilic drug has given this colloidal system a valuable position in drug delivery. This article contains information on components required for its fabrication, preparation methods and evaluation parameters along with its application in drug delivery and future aspects of this advanced drug delivery system.
Keywords: nanoemulsion; bioavailability; HLB; surfactants; drug delivery